THE EFFECT OF APPLICATION OF SLEEP TRAINING METHODS WITH POSITIVE ROUTINES ON THE QUALITY OF SLEEP OF INFANTS AGED 3-4 MONTHS AT THE VILLAGE HEALTH CENTRE MULYOGAGUNG - DAU MALANG DISTRICT - Purwanti, Anik Sri; Nabilla, Anggita Cantika; Maulina, Rifzul (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
Factors affecting the growth and development of babies include sleep and rest. The quality of a baby's sleep is influenced by various factors such as the environment, nutrition, illness, and physical activity. This study aimed to investigate the impact of positive sleep training methods on the sleep quality of 3-4-month-old babies at the Mulyoagung Village Health Post. The study involved a population of 50 babies, with a sample of 36 babies. Data was collected through pre-test and post-test questionnaires, and the analysis involved univariate methods like frequency distribution and bivariate methods like Wilcoxon. The research demonstrates the changes by implementing positive sleep training for babies aged 3-4 months at the village health post in Mulyoagung. The results of the Wilcoxon test showed a significant result of 0.000 (p 0.005), indicating that the implementation of positive routine sleep training methods influenced the sleep quality of babies aged 3-4 months. It is recommended that parents use positive routine sleep training methods to enhance the bond between babies and their parents.